Physicochemistry properties of water treatment sludge (WTS) as adsorbents for dyes and antibiotics removal - Saman, Norasikin; Subramanian, Kavij Kumar; Johari, Khairiraihanna; Mat Taib, Shazwin; Marčiulaitienė, Eglė (International Conference “Environmental Engineering”, 2023)
Application of waste materials as adsorbent for water treatment has obtained special attention owning to their low cost and surface functionality. In this study the waste-treatment sludge (WTS) sludge was selected as based materials and used as adsorbents for dyes and antibiotic adsorption. The adsorbent was prepared by calcination of the washed and dried WTS adsorbent (S105) at 300 °C (S300) and 700 °C (S700). The morphology, elemental composition, functional groups, pH at point zero charged, and cationic exchange capacity were observed and evaluated to understand the adsorption performance capability of the adsorbents. Then, the adsorbents were test for dyes and antibiotic adsorption in aqueous solution. Adsorbent prepared at higher temperature have darker color. The FTIR peaks related to functional groups of organic compounds such as OH and CO were diminished when the WTS was calcined at 700 °C. Value of pHpzc of of S105, S300 and S700 were 5.43, 5.81 and 5.89, respectively. The value of CEC for S700 and S105 however lower than S300. Adsorption performance of WTS adsorbents towards cationic methylene blue (MB), anionic methyl orange (MO) and reactive red-120 was evaluated in aqueous solution. All adsorbents show high adsorption performance towards MO, but lower adsorption performance towards RR was observed. The calcination of WTS results the higher adsorption capacity observed for adsorption of anionic and cationic dyes. The S700 also show better adsorption performance towards OTC and TC. This study indicates that the WTS has a potential application as low-cost adsorbent to remove hazardous substances from aqueous solution.